The Benefit of Public speaking for Bujang Gadis Palembang as Tourism Ambassador for Palembang City - Rahma, Munaja; Sari, Rindi Yunita; Zakaria; Darmaliana; Yeny, Eli (Politeknik Negeri Sriwijaya, 2023)
Abstract: The purpose of this study was to find out how the public speaking role of Bujang Gadis Palembang was as a tourism ambassador for the city of Palembang. In this qualitative study, all participants were approached using snowball sampling. There were 23 participants, all of whom participated in individual in-depth interviews. The data collected from all interviews were analyzed using thematic analysis techniques. Interview data revealed that the role of Bujang Gadis Palembang's public speaking was very influential on tourism in the city of Palembang. Public speaking Bujang Gadis Palembang also plays a role in promoting tourism in the city of Palembang. However, no data was found to be ineffective because all participants agreed that the role of public speaking had a positive effect on promoting tourism in the city of Palembang. Keywords: role, public speaking, Bujang Gadis Palembang, tourism